Performance of a laboratory-scale microalgae pond for secondary treatment of distillery wastewaters - Travieso, L. (Array, 2008)
Summary: Distillery waste disposal is one of the major problems being faced by all nations across the globe. To diminish its organic loading, the distillery waste is treated before its final disposal by biological processes. Microalgae pond gives a way to solve this situation. An evaluation of the performance of a laboratory-scale microalgae pond treating distillery waste previously treated in an anaerobic filter was carried out. The microalgae pond operated with an effluent recycling (R) of 10:1 with respect to the influent and at an hydraulic retention time (HRT) of 11 days based on the mixture (influent + recycling). The surface organic loading rates (SOLR) used were G = 418 kg COD ha–1 d–1 and G = 92 kg BOD5 ha–1 d–1 according to the literature recommendations for microalgae ponds. Total chemical oxygen demand (COD), biochemical oxygen demand (BOD5), total solids (TS), total suspended solids (TSS), volatile suspended solids (VSS), total nitrogen, ammonia, total chlorophyll ( C,T) and chlorophyll a ( ca) concentrations were monitored. COD and BOD5 removals of 83.2 % and 88.0 %, respectively were obtained. Removals of 60.6 %, 53.4 % and 78.8 % in the TS, TSS and VSS concentrations were achieved. The possibility to grow microalgae for biomass in this waste was also evaluated using the determinations of chlorophyll a ( ca) and VSS